The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1109/ted.2010.2050961
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Reliability Study of Single-Layer and Dual-Layer Platinum Nanocrystal Flash Memory Devices Under NAND Operation

Abstract: Abstract-Memory window (MW) and the retention of singlelayer (SL) and dual-layer (DL) platinum (Pt) nanocrystal (NC) devices are extensively studied before and after program/erase (P/E) cycling. DL devices show better charge storage capability and reliability over the SL devices. Up to 50% improvement in the stored charge is estimated in the DL device over SL when P/E is performed at equal field. Excellent high temperature and postcycling retention capabilities of SL and DL devices are shown. The impact of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(48 reference statements)
0
6
0
1
Order By: Relevance
“…As a catalyst, Pt nanodots have been extensively used in the petroleum reforming and petrochemical industries as well as in fuel cells because of their excellent catalytic activity [1-4]. On the other hand, Pt nanodots have also been investigated for memory devices that utilize discrete metal nanodots as charge storage medium [5,6]. This is attributed to the potential that the nanodot-based memories can lessen the impact of localized oxide defects, lateral coupling of charge storage layers between adjacent devices, and stress-induced leakage current [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a catalyst, Pt nanodots have been extensively used in the petroleum reforming and petrochemical industries as well as in fuel cells because of their excellent catalytic activity [1-4]. On the other hand, Pt nanodots have also been investigated for memory devices that utilize discrete metal nanodots as charge storage medium [5,6]. This is attributed to the potential that the nanodot-based memories can lessen the impact of localized oxide defects, lateral coupling of charge storage layers between adjacent devices, and stress-induced leakage current [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the employment of Pt nanodots can obtain a deep potential well in memory devices to ensure good data retention, together with good compatibility with CMOS processing. However, most researchers used high-temperature rapid thermal annealing (RTA) of ultrathin Pt films to achieve high-density Pt nanodots [5,8,9], which might cause the formation of an additional interfacial layer between the high-permittivity (high- k ) tunnel layer and silicon substrate as well as crystallization of the tunnel layer.…”
Section: Introductionmentioning
confidence: 99%
“…1 A novel structure adopting a single layer (SL) or dual layer (DL) metal nanocrystal (MNC) as localized charge storage medium has been proposed as a candidate for sub-22 nm flash memory cell. 2 Besides the possibility of scaling below 22 nm, the discrete individual charge storage nodes (i.e., MNCs) also provide better immunity to defects than conventional floating gate flash memory. 3 In particular, it has been reported that stacks containing DL MNC provide an enhanced memory window over SL MNC and have the potential capability of storing multi-bits per cell for the future NAND flash applications.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic NDs have received much attention because of their potential application to charge storage devices 24 25 26 27 28 29 30 31 32 33 34 . The charging and discharging characteristics of metallic NDs through an ultrathin oxide layer depend on their electrostatic potential.…”
mentioning
confidence: 99%